Strengthening Economic Innovation in Vietnam: A SWOT Analysis of Research and Development Role and Impact - Huy, Dinh Tran Ngoc; Dung, Pham Anh; Nuong, Le Ngoc; Han, Le Thi; Hien, Dinh Tran Ngoc; Nhan, Pham Hung (Journal Development Manecos, 2024)
This research aims at analyzing Research and Development (R&D) for economic innovation in Vietnam, the opportunities and challenges for enhancing the partnership between public and private sector institutions and universities. In this work, adopting an analytical and descriptive approach, historical analysis, document, and comparative analysis, we assessed the existing framework for R&D in Vietnam and its contribution to the country’s economic growth. The results highlighted the fact, where Vietnam has succeeded in constructing the public R & D network, especially through governmental funding to institutes but the interaction between the public and private sectors has still a long way ahead. Cross-sectional studies between South Korea and Taiwan illustrated that public-private partnerships and university collaboration important for advancement of the innovation capacity and economic growth. The study also looks into the issues of obsolescence of equipment and technology, low private sector participation and problems of technology transfers in the global market. Thus, it is recommended that Vietnam should compliment its R&D environment by benchmarking to such models, identifying specific sectoral linkage, and increasing R&D investment in the relevant sectors. In this way, Vietnam can improve the role and efficiency of R&D with an aim to enhance productivity, and thus enhance the competitiveness and sustainable economic growth.